2021
DOI: 10.12688/wellcomeopenres.16431.2
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare use by people who use illicit opioids (HUPIO): development of a cohort based on electronic primary care records in England

Abstract: Background: People who use illicit opioids such as heroin have substantial health needs, but there are few longitudinal studies of general health and healthcare in this population. Most research to date has focused on a narrow set of outcomes, including overdoses and HIV or hepatitis infections. We developed and validated a cohort using UK primary care electronic health records (Clinical Practice Research Datalink GOLD and AURUM databases) to facilitate research into healthcare use by people who use illicit op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…First, our sample of patients from general practices might not represent the population of people who use illicit opioids in England. In a validation study, 18 we found the cohort had similar demographic characteristics and mortality rates as other studies of people who use illicit opioids, and 90% of patients being treated in hospital who received a diagnosis of opioid dependence were also captured by primary care records. This suggests that the cohort represents people with more severe opioid use or dependence but might under-represent people who use opioids for shorter periods, less frequently, or have not sought treatment.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…First, our sample of patients from general practices might not represent the population of people who use illicit opioids in England. In a validation study, 18 we found the cohort had similar demographic characteristics and mortality rates as other studies of people who use illicit opioids, and 90% of patients being treated in hospital who received a diagnosis of opioid dependence were also captured by primary care records. This suggests that the cohort represents people with more severe opioid use or dependence but might under-represent people who use opioids for shorter periods, less frequently, or have not sought treatment.…”
Section: Discussionmentioning
confidence: 85%
“…We have previously published a full codelist and validation showing that this sample has similar demographic characteristics and all-cause mortality rates as other samples of people who use illicit opioids (eg, heroin) or are receiving opioid agonist therapy. 18 The entry date was Jan 1, 2001; 12 months after entry to CPRD; or the first record of illicit opioid use. We used a washout of 12 months to avoid the unusual period after joining a database such as CPRD because this period often coincides with registration at a doctor's surgery and might be associated with poor health, diagnosis, or recording of pre-existing health problems.…”
Section: Methodsmentioning
confidence: 99%
“…These observations are recorded by GPs either during a clinical consultation or following information shared with the GP from another health service. We previously published the full code list and showed that patients meeting these criteria have similar characteristics to other samples of people who use illicit opioids in the United Kingdom, including an increasing average age (currently in the early 40%), approximately 70% being male, and very high mortality rates [19]. We excluded participants with no recorded sex (0.002%).…”
Section: Participantsmentioning
confidence: 99%
“…There is a large corpus of observational research on opioid use and safety among the elderly worldwide, including studies based in the United States, [13][14][15] Canada, 16,17 and Europe. [18][19][20][21] However, it is not known whether these data sources were used to study opioid use in nursing homes (NHs).…”
Section: Introductionmentioning
confidence: 99%